Contemporary management of ureteral strictures. (January 2019) - Vasudevan, Vinaya P; Johnson, Emmanuel U; Wong, Kee; Iskander, Morkos; Javed, Saqib; Gupta, Nikhil; McCabe, John E; Kavoussi, Louis
Ureteral stricture disease is a luminal narrowing of the ureter leading to functional obstruction of the kidney. Treatment of strictures is mandatory to preserve and protect renal function. In recent times, the surgical management of ureteral strictures has evolved from open repair to include laparoscopic, robotic and interventional techniques. Prompt diagnosis and early first line intervention to limit obstructive complications remains the cornerstone of successful treatment. In this article, we discuss minimally invasive, endo-urological and open approaches to the repair of ureteral strictures. Open surgical repair and endoscopic techniques have traditionally been employed with varying degrees of success. The advent of laparoscopic and robotic approaches has reduced morbidity, improved cosmesis and shortened recovery time, with results that are beginning to mirror and in some cases surpass more traditional approaches. Level of evidence: Not applicable for this multicentre audit.